Biosimilar Medicines - Hue Linh, Nguyen; Thanh Hai, Nguyen; Dang Khoa, Nguyen; Quoc Anh, Vo; Hue, Pham Thi Minh (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 1DO - 10.25073/2588-1132/vnumps.4751, 2025)
Biosimilars/biosimilar medicines have been developing rapidly, promising to bring many benefits in the diagnosis, treatment, prevention of diseases, and human health improvement. Biosimilar is a medicine that is highly similar to an already licensed biological product (reference medicine). Although there are some minor differences in the inactive ingredients, there are no clinically significant differences in the purity, potency, and safety between the two products. The development of biosimilars is a challenging multistep process. Unlike "generic" medicine, the development of biosimilars requires comprehensive studies to demonstrate comparability to the reference medicine and to ensure safety and efficacy. Therefore, there are many unique characteristics in the research and development, biological activity testing, approval, and quality control of biosimilars. This review discusses the characteristics of biosimilar medicines and the challenges in their research, development, and approval.